Fifty years of Indian History Congress : a micro-index - Das, S. P. (Sakti Pada) (Delhi : S.S. Publishers, 1986)
Comprises author and subject indexes to the proceedings of the Indian History Congress.
v. 1. 1935-1947 -- v. 2. 1948-l957.
Spine title: 50 years of Indian History Congress.
Keywords: Indian History Congress -- Bibliography; India -- History -- Congresses -- Indexes